Consonant Confusion: Pronunciation Challenges among English Club Members - Dewi, Ni Komang Nira; Hikmaharyanti, Putu desi Anggerina (Universitas Muhammadiyah Mataram, 2025)
This study examines pronunciation errors among university students learning English as a second language, focusing on members of the English Club, primarily Balinese learners. Despite English being a global language and widely learned as a second language, pronunciation remains a significant challenge, often influenced by the learners' native language. This research employs a qualitative approach with purposive sampling to select a sample of 11 participants who are not majoring in English. These participants were chosen through observation and a questionnaire. Data are collected by having the participants read a story,